Guided self-study in preclinical physiotherapy students -- A feasibility study. - Schenk, Elisabeth; Taeymans, Jan; Rogan, Slavko (South African Journal of Physiotherapy, 2023)
Background: Literature describing the impact of guided self-study (G-SS) in knowledge changes and skills improvements in undergraduate students is scarce. Objectives: The aims of our study were to evaluate the feasibility of a G-SS programme in a full-time undergraduate physiotherapy degree course and to assess the effectiveness of the G-SS on changes in knowledge and development of skills (hands-on). Method: Fifty-three first-semester undergraduate physiotherapy students were randomly divided into a G-SS group and a control group (CG). The G-SS group received six clinical cases and prepared each case during an 8-day cycle. The control group received self-study learning units of the original curriculum content. Primary outcome parameters were (1) time of task, (2) responsiveness of students and (3) programme differentiation. Knowledge changes and skills changes were tested using a multiple-choice questionnaire and the objective structured clinical examination (OSCE). Results: Students' responsiveness was 32%. This was below the a priori set 83%. No differences in programme differentiation were found. The OSCE grade was significantly higher in the G-SS compared to CG (p = 0.003). Conclusion: The G-SS programme in its current form was not feasible regarding students' responsiveness. Therefore, a slight modification of our study protocol (e.g., better time planning in the academic calendar) is needed to improve students' willingness to participate in the G-SS programme. Clinical implications: Adaptation of the school timetable should allow undergraduate physiotherapy students to prepare clinical cases under conditions of lower workload. Guided self-study as compared to CG is superior in knowledge change and (hands-on) skills improvement.